Immunological Identification and Characterization of the Capsid Scaffold Protein Encoded by UL26.5 of Herpes Simplex Virus Type 2 - Li, Xueqi; Wang, Jianbin; Mou, Tangwei; Gao, Yang; Wang, Lichun; Fan, Shengtao; Xu, Xingli; Jiang, Guorun; Cui, Pingfang; Xu, Xiangxiong; Duan, Suqin; Zhang, Jingjing; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Herpes simplex virus type 2 (HSV2), a pathogen that causes genital herpes lesions, interferes with the host immune system via various known and unknown mechanisms. This virus has been used to study viral antigenic composition. Convalescent serum from HSV2-infected patients was used to identify viral antigens via 2-D protein electrophoresis and immunoblotting. The serum predominantly recognized several capsid scaffold proteins encoded by gene UL26.5, mainly ICP35. This protein has been primarily reported to function temporarily in viral assembly but is not expressed in mature virus particles. Further immunological studies suggested that this protein elicits specific antibody and cytotoxic T lymphocyte (CTL) responses in mice, but these responses do not result in a clinical protective effect in response to HSV2 challenge. The data suggested that immunodominance of ICP35 might be used to design an integrated antigen with other viral glycoproteins.